2014 48th Asilomar Conference on Signals, Systems and Computers 2014
DOI: 10.1109/acssc.2014.7094804
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of self-body blocking effects in millimeter wave cellular networks

Abstract: The millimeter wave (mmWave) spectrum is a strong candidate carrier frequency for access channels in fifth generation cellular networks. Unfortunately, the human body heavily attenuates mmWave signals. This paper evaluates the impact of self-body blocking (the blocking of the direct link by the handset user's body) in mmWave cellular networks using a stochastic geometric network model. A mathematical model for self-body blocking is proposed, allowing for position changes, and used to compute signal-to-interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 11 publications
0
54
0
1
Order By: Relevance
“…Dense mmWave networks have been widely studied for outdoor scenarios [6], [15]- [17] and much of the blockage modelling and their results are used for studying indoor scenarios as well. In [17], Bai and Heath have shown that there is a finite optimal AP density for coverage, with fixed AP and UE beamwidth configurations, which is given by the transition from a noise-limited regime to an interferencelimited regime when increasing AP density.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Dense mmWave networks have been widely studied for outdoor scenarios [6], [15]- [17] and much of the blockage modelling and their results are used for studying indoor scenarios as well. In [17], Bai and Heath have shown that there is a finite optimal AP density for coverage, with fixed AP and UE beamwidth configurations, which is given by the transition from a noise-limited regime to an interferencelimited regime when increasing AP density.…”
Section: Related Workmentioning
confidence: 99%
“…Yet, coverage can still be deteriorated by human bodies, as they introduce as much as 40 dB of attenuation [4]- [6], which may be enough to lose the connection between AP and UE. In order to combat the detrimental effects of blockages, one would be tempted to increase the AP density to maintain connectivity [6]. However, here comes another challenge -inter-cell interference.…”
Section: Introductionmentioning
confidence: 99%
“…A mmWave link may have three kinds of blockages, namely, static, dynamic, and self-blockage. Static blockage due to buildings and permanent structures has been studied in [12] and [13] using random shape theory and a stochastic geometry approach for urban microwave systems. The underlying static blockage model is incorporated into the cellular system coverage and rate analysis in [3].…”
Section: Related Workmentioning
confidence: 99%
“…A statistical self-blockage model is developed in [17] through experiments considering various modes (landscape or portrait) of handheld devices. The impact of self-blockage on received signal strength is studied in [13] through a stochastic geometry model. They assume the self-blockage due to a user's body blocks the BSs in an area represented by a cone.…”
Section: Related Workmentioning
confidence: 99%
“…This phenomena gives HBB a high dependency on the system deployment, especially on the height of antenna installation. Yet most current available models are either two-dimensional [13,14], or specified to some particular system deployment [15], or even empirically instead of physically built [17]. Therefore, they cannot fulfill the requirements of flexibly modeling HBB events in variant outdoor scenarios.…”
Section: Introductionmentioning
confidence: 99%